Revisiting khilāfah: the role of nonpolitical social factors in good governance - Solihu, Abdul Kabir Hussain (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2014)
Abstract: Khilāfah has been a symbol of the Muslim political system and Islamic politics has often been identified as Khilāfah in the same structure it took form in the past. This study argues that Muslims exhausted their energy on political discourse at the expense of other factors which are important for preparing the ground for political maturity. An attempt is made to exhibit normativeness of the Islamic political principles and values and the historicity of the form (Caliphate) it has acquired over the course of Islamic history. Furthermore, greater emphasis is placed on the broader, civilisational sense of Khilāfah under which the political sense of Khilāfah (Caliphate) is subsumed. In doing so, the study aims to contribute to the discourse on the revitalisation of the contemporary Muslim political culture but through non-political means.